ONLINE PERCEPTION OF ARTIFICIAL REEF RISK AND SAFETY BY STAKEHOLDERS (INCLUDING RESIDENTS AND TOURISTS) VIA THE ANALYTIC HIERARCHY PROCESS - Jorge Ramos (Journal of Spatial and Organizational Dynamics, 2021)
Artificial reefs (AR) may be ignored by many people, probably because they are usually unseen structures. Even so, there are users that believe in the value of these structures even without observing them, as is the case of most fishermen and anglers. Divers usually believe in AR and are the ones effectively able to notice them. Based on the previous simple premises, the aim of this paper is to ascertain the perception coastal community people and tourists have on the risks and benefits derived from the presence of AR nearby. AR were deployed off the Algarve from 1990 to 2003. The methodological approach for sampling purposes used a search engine with key-terms following a simple 3-step protocol: identification, screening, and eligibility. The eligible documents were analysed using qualitative data analysis software. Most documents found were from AR promoters named as “institutional” and communication “media” reporting mostly AR by the supply side. Sources from companies named as “firms” and discussion “fora” were mostly on the demand side. The contents of the samples were assigned onto two different categories: risk and safety. These derived into the relevant criteria where alternatives were judged to achieve the goal stated in the analytic hierarchy process (AHP). AHP sensitivity analyses were carried out and the best choices were calculated.